Importance And Spread of Mosh Varieties - Kobilov Sokhibjon Sherovich; Ghoziyev Makhamadali Anorbayevich; Muqimov Zohidjon Alijonovich; Kholikov Mukhridin Bakhromjon ogli (Academia One, 2024)
This article provides information about the importance, origin, distribution and varieties of the Mosh plant.
Keywords: Durdona; Navroz; Kahraba; Radost